Islamic Religious Education Teacher Strategy in Utilizing the YouTube Application as a Learning Media in Class XI Computer and Network Technology - Mohammad Choirudin Umar; Sofyan Tsauri; St Rodliyah (LPPM Universitas PGRI Sumatera Barat, 2024)
In the world of education, YouTube is a source, material and learning media that can be used by educators, students, school staff and even parents as an alternative media in finding and helping to find the resources needed. The research focus in this thesis is: 1) What is the teacher's strategy in using the YouTube application as a PAI learning medium in class X1 TKJ 1 SMKN 5 Jember? 2) What are the obstacles for teachers in implementing the use of the YouTube application as a PAI learning medium in class X1 TKJ 1 SMKN 5 Jember? 3) What is the impact of implementing teacher strategies in PAI subjects for students in class X1 TKJ 1 SMKN 5 Jember on students? The objectives of this research are: 1) To describe the teacher's strategy in using the YouTube application as a learning medium in PAI learning in class X1 TKJ 1 SMKN 5 Jember. 2) To describe the obstacles teachers face in implementing the use of the YouTube application as a learning medium in PAI learning in class X1 TKJ 1 SMKN 5 Jember. 3) To describe the impact on students in implementing teacher strategies in PAI subjects in class X1 TKJ 1 SMKN 5 Jember. This research uses a qualitative approach with descriptive research type, data collection methods namely observation, interviews and documentaries. Meanwhile, the data analysis method starts from data condensation, data presentation, and drawing conclusions/verification. Validity of data using triangulation of sources and methods. This research concludes: 1) The teacher's strategy in using the YouTube application is in three stages, namely: First, preparing for learning and understanding the material, as well as making learning videos. Second, carry out learning by watching and listening to videos, taking notes and summarizing the material, then holding discussions and asking questions. Third, evaluation. 2) There are three obstacles for teachers in implementing the use of the YouTube application. First, signal interference and school WiFi. Second, the resolution quality is low. Third, inadequate technological equipment. 3) the positive impact of PAI teachers' use of strategies using YouTube media, namely: students become more enthusiastic, more capable and responsive, students are less literate in IT technology, and YouTube is a source of student learning. Meanwhile, the negative impact is: students watch videos in addition to their school assignments, and neglect their main school assignments.